Structural Members and Frames. - Galambos, T. V. (Dover books on engineering, 2016)
Geared toward graduate students and professionals in structural engineering, this text presents a detailed treatment of the elastic and inelastic behavior of metal beams, columns, beam-columns, and rigid frames. All four topics receive separate chapters, in which the background for their general behavior is discussed in terms of specific structural tests. The chapters also examine theoretical elastic behavior and the termination of usefulness by elastic buckling, behavior in the inelastic region, and the uses of various conceptual models in predicting inelastic instability. The final section of each chapter covers procedures and provides interpretations of structural specifications. Two additional chapters offer an introduction to the text and derive the differential equations governing the elastic deformations of prismatic thin-walled open members. Numerous examples throughout the treatment illustrate theory and applications.